Representasi Gunung Kemukus dalam Konten Media Sosial oleh ‎Konten Kreator - Fathurohmah Putri Dzikriyah; Siany Indria Liestyasari (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
This study examines how Mount Kemukus is represented in TikTok content produced by content creators and explores how audiences interpret these representations. The study addresses the persistent tension between cultural-religious narratives and the negative stereotypes that continue to shape the site's public image. Employing a descriptive qualitative approach grounded in Stuart Hall’s theory of representation, data were collected through observations of TikTok content, documentation, interviews with content creators and audiences, and analyses of user comments. The findings reveal three dominant representations of Mount Kemukus: a site of religious, cultural, and historical tourism; a family tourism destination; and a location associated with pesugihan rituals. These representations are constructed through visual imagery, captions, narration, music, and symbolic elements embedded in creators’ encoding practices. Audience interpretations vary across dominant-hegemonic, negotiated, and oppositional readings. While some audiences reproduce the site's negative stigma, others reinterpret it based on personal experience, and local communities largely reject the stigmatizing narratives by emphasizing Mount Kemukus as a religious, cultural, and historical heritage destination. The study argues that social media functions not merely as a platform for information dissemination but also as a dynamic arena for constructing, contesting, and reproducing cultural meanings, stereotypes, and collective identities.